Liability Of A Doctor Who Perform A Malpractice (A Review Under Health Law) - Benny L.H Hutahaean (Journal of Law Science, 2022)
The problems that will be discussed by the author in the writing of this thesis are: What are the limitations that can be used to determine that a doctor has committed medical malpractice on a patient; What actions or legal remedies can a patient or his family take if he is exposed to medical malpractice; What sanctions can be imposed on doctors who commit medical malpractice as a form of responsibility of doctors to their patients. The type of research used in this paper is a normative juridical research, namely research conducted on written regulations governing health law and legal materials related to medical malpractice. In discussing medical malpractice involving two different disciplines, namely medical science and health science, this paper will use the "medicolegal approach" which is a way of approaching medical problems through law. Medical malpractice is every action of a doctor (whether intentionally or unintentionally such as negligence, negligence) in carrying out a medical practice, which is not in accordance with medical ethics, medical professional standards, applicable laws and regulations so as to cause harm to the patient such as pain, injury, disability, death and other loss; and for his actions, the doctor must be responsible under administrative law and/or civil law and/or criminal law. Legal remedies that can be taken by patients (or their families) who experience medical malpractice actions consist of: Complaining to MKDKI; suing the doctor; Through the Criminal Court. Doctors who commit medical malpractice may be subject to sanctions based on administrative law and/or civil law and/or as a form of legal liability.